2014
DOI: 10.1371/journal.pone.0106378
|View full text |Cite
|
Sign up to set email alerts
|

Nogo Receptor Inhibition Enhances Functional Recovery following Lysolecithin-Induced Demyelination in Mouse Optic Chiasm

Abstract: BackgroundInhibitory factors have been implicated in the failure of remyelination in demyelinating diseases. Myelin associated inhibitors act through a common receptor called Nogo receptor (NgR) that plays critical inhibitory roles in CNS plasticity. Here we investigated the effects of abrogating NgR inhibition in a non-immune model of focal demyelination in adult mouse optic chiasm.Methodology/Principal FindingsA focal area of demyelination was induced in adult mouse optic chiasm by microinjection of lysoleci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…Xu and others reported that the third ventricle ependymal layer cells were able to migrate into hypothalamic parenchymal regions and differentiate into functional neurons in response to injury (172). Our previous study also showed that progenitor cells in the third ventricle surroundings could be reactivated by local demyelination in the optic chiasm (128,171). Also nestin and DCX-positive cells have been found in the meninges of the brain and spinal cord (138,173).…”
Section: Other Germinal Areas Of the Cnssupporting
confidence: 50%
See 1 more Smart Citation
“…Xu and others reported that the third ventricle ependymal layer cells were able to migrate into hypothalamic parenchymal regions and differentiate into functional neurons in response to injury (172). Our previous study also showed that progenitor cells in the third ventricle surroundings could be reactivated by local demyelination in the optic chiasm (128,171). Also nestin and DCX-positive cells have been found in the meninges of the brain and spinal cord (138,173).…”
Section: Other Germinal Areas Of the Cnssupporting
confidence: 50%
“…Certain antidepressants like fluoxetine have been revealed to be capable of increasing neurogenesis (203). Administration of small interfering RNA (siRNA) or specific antibodies against various inhibitory targets such as Nogo, Nogo receptor (NgR), LINGO1, and Sema3A in different animal models of MS and spinal cord injury enhance proliferation, migration, and differentiation potential of endogenous stem cells and facilitate axonal regeneration, myelin repair, and functional recovery (128,(204)(205)(206)(207). Khezri and coworkers reported that administration of cyclic AMP inhibits the progression of EAE disease and potentiates recruitment of endogenous NSCs and myelin repair (208).…”
Section: Endogenous Neural Stem Cell Niche Modulation As a Therapeutimentioning
confidence: 99%
“…12,18,19 VEP has been used in animal models to assess neurological or potential eff ects on remyelination of the adenosine A1 receptor agonist N6-cyclohexyladenosine and siRNAs against the Nogo receptor. 20,21 VEP was also used in single or small multicentre clinical studies assessing high-dose intravenous immunoglobulin, erythropoietin, simvastatin, and phenytoin in patients with acute optic neuritis, [22][23][24][25] and in natural recovery observational studies after an acute optic neuritis episode. 12,16,17,[26][27][28] When baseline characteristics of participants enrolled in RENEW were compared with those in trials of other candidate remyelinating or neuroprotective drugs, age and percentage of women were similar, mean number of days from fi rst acute optic neuritis symptom to fi rst dose was 24 days in RENEW versus 5-20 days in previous acute optic neuritis studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that NogoA plays a direct role in regulating myelination in vitro and in an in vivo model of focal demyelination (Chong et al, 2012). Furthermore, blocking NgR1 significantly enhanced the remyelination process, recruitment of proliferating OPC to the lesion site, and functional recovery after demyelination in the optic nerve (Pourabdolhossein et al, 2014). The mechanism for NgR1-mediated inhibition of neurite outgrowth involves activation of RhoA and its downstream effector Rho kinase ROCK (Niederost et al, 2002), however, whether this mechanism also plays a role in the regulation of OPC and remyelination is still unknown.…”
Section: Molecular Pathways Involved In Ischemic White Matter Damamentioning
confidence: 99%